2020
DOI: 10.1186/s12967-020-02452-3
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic review of mitochondrial abnormalities in myalgic encephalomyelitis/chronic fatigue syndrome/systemic exertion intolerance disease

Abstract: Background Patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) or Systemic Exertion Intolerance Disease (SEID) present with a constellation of symptoms including debilitating fatigue that is unrelieved by rest. The pathomechanisms underlying this illness are not fully understood and the search for a biomarker continues, mitochondrial aberrations have been suggested as a possible candidate. The aim of this systematic review is to collate and appraise current literature on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 47 publications
(221 reference statements)
0
40
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified errors in the Results section, in the Discussion section and in Tables 2 and 4.…”
Section: Correction To: J Transl Med (2020) 18:290 101186/s12967-020mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified errors in the Results section, in the Discussion section and in Tables 2 and 4.…”
Section: Correction To: J Transl Med (2020) 18:290 101186/s12967-020mentioning
confidence: 99%
“…A recent systematic review investigated mitochondrial dysfunction in ME/CFS patients compared with healthy controls (HC)[ 28 ]. Although disruptions to mitochondrial pathways were documented including changes in mitochondrial respiratory function, metabolites and coenzymes, there was a lack of consistency across the studies, including results and study designs [ 9 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review investigated mitochondrial dysfunction in ME/CFS patients compared with healthy controls (HC)[ 28 ]. Although disruptions to mitochondrial pathways were documented including changes in mitochondrial respiratory function, metabolites and coenzymes, there was a lack of consistency across the studies, including results and study designs [ 9 28 ]. Furthermore, with the low numbers of studies in this field it is difficult to derive appropriate conclusions for mitochondrial dysfunction for the pathomechanism of ME/CFS [ 9 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations